Focusing of intense pulsed ion beam by magnetically insulated diode for material research - Yu, Xiao; Zhang, Shijian; Stepanov, Andrey Vladimirovich; Shamanin, Vitaly Igorevich; Zhong, Haowen; Liang, Guoying; Xu, Mofei; Zhang, Nan; Kuang, Shicheng; Ren, Jianhui; Shang, Xuying; Yan, Sha; et al. (Surface & coatings technology, 2020)
The cross-sectional distribution and focusing properties of intense pulsed ion beam by an active magnetically insulated diode for material modification is presented. The ion beam accelerator BIPPAB-450 uses the surface flashover of polymers as the ion source, generates intense pulsed ion beam composed of protons and carbon ions with a pulse length of 120 ns, ion energy up to 450 keV, energy density up to 3 J/cm2. By the strong flash thermal effects on the surface of materials, the ion beam can be used for the surface treatment and ablation related application. The cross-sectional distribution of the ion beam was measured by infrared imaging method. The results on the focusing of the diode reveal the distribution in the plasma generation on the anode surface. Comparative study on beam focusing during transportation was made and it is demonstrated that by using a copper beam limiter, the maximum beam energy density can be increased by a factor of nearly 1.5. The change in the beam phase-space distribution by the limiter is also exhibited and the influence on beam diagnostics and optimization is discussed reasonably. •Beam maximum energy density increased by 50% with a metal cone beam limiter.•Phase-space distribution better kept with beam limiter from the ion source.•Beam density increased with total energy decreased with beam limiter.